Anarchy and legal order : law and politics for a stateless society - Chartier, Gary (Cambridge : Cambridge University Press, 2013)
'This book develops and defends the idea of law without the state. Animated by a vision of peaceful, voluntary cooperation as a social ideal and building on a careful account of non-aggression, it features a clear explanation of why the state is illegitimate, dangerous, and unnecessary. It proposes an understanding of how law enforcement in a stateless society could be legitimate and what the optimal substance of law without the state might be, suggests ways in which a stateless legal order could foster the growth of a culture of freedom, and situates the project it elaborates in relation to leftist, anticapitalist, and socialist traditions'--Provided by publisher.
Laying foundations -- Rejecting aggression -- Safeguarding cooperation -- Enforcing law -- Rectifying injury -- Liberating society -- Situating liberation
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Rule of law; State, The; Anarchism